The Huayruro Project: mapping the Calicanto Inca area buried by the A.D. 1600 Huaynaputina eruption, with geophysical imaging and remote sensing - Antoine, Raphael (2018)
We present geophysical and remote sensing observations near the Quinistaquillas town (southern Peru), in the framework of the HUAYRURO Project. This Inca zone was buried during the A.D. 1600 Huaynaputina eruption, the most important volcanic phenomenon of the last 400 years. The eruption had a global impact, due to the volume of emitted ash (2-3 times the one emitted by Vesuvius in A.D. 79). This lead to a 1.13°C cooling of the planet and caused a worlwide agricultural crisis. During the eruption, the Calicanto-Chimpapampa zone was covered by ashes and pyroclastic flows, with a thickness in the range [1 - 20] m. From 2015 to 2017, remote sensing and geophysical methods were deployed to map a ~ 1 km*2 km area, up to 3-m depth.